Harvard business review on change (Harvard Business School P. BostonUS, 1998)
Discusses 8 reasons why some corporate change initiatives have failed. Suggests that companies preserve core values and a core purpose, but simultaneously stimulate progress. Proposes the redefining of workers' personal compacts as a solution to their resistance to workplace change. Advocates results-driven improvement programmes and gives pointers on how to get started.
Located in the Learning Resource Centre